Assessing The Effectiveness Of FPS Gamification In Arabic Acquisition for Integrated Islamic Elementary Schools Students - Suryadarma, Yoke; Ismail, Moh.; Pradhana, Faisal Reza; Rini, Fitri Setyo (Ijaz Arabi Journal of Arabic Learning, 2025)
This study investigates the effectiveness of 3D First-Person Shooter (FPS) gamification on Arabic learning for Integrated Islamic elementary school (SDIT) students. The primary goal is to assess how this interactive learning medium improves students' Arabic language proficiency and to evaluate the satisfaction levels of both students and teachers. Utilizing a mixed-methods approach, the research combines qualitative and quantitative data collection techniques. Pretest-posttest assessments are used to measure students' progress before and after engaging with the gamified media, while questionnaires capture satisfaction and feedback from participants. Results show a significant improvement in students' Arabic vocabulary, with average scores increasing from 74.1 in the pre-test to 89.2 in the post-test. A paired sample t-test confirmed the improvement as statistically significant (p < 0.001). The results of surveys showed high satisfaction levels, with students expressing motivation and enthusiasm for learning and teachers recognizing the game’s relevance and effectiveness in classroom settings. These findings suggest that 3D FPS-based gamification enhances Arabic language learning in Islamic elementary schools. The study recommends further exploration of gamification techniques in Arabic education at various academic levels.